Proceedings of the 16th International ACM SIGACCESS Conference on Computers &Amp; Accessibility - ASSETS '14 2014
DOI: 10.1145/2661334.2661356
|View full text |Cite
|
Sign up to set email alerts
|

Age, technology usage, and cognitive characteristics in relation to perceived disorientation and reported website ease of use

Abstract: Comparative studies including older and younger adults are becoming more common in HCI, generally used to compare how these two different age groups will approach a task. However, it is unclear whether user 'age' is the underlying factor that differentiates between these two groups. To address this problem, an examination into the relationship between users' age, previous technology experience, and cognitive characteristics is conducted. Measures of perceived disorientation and reported ease of use are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Our dependent variables included the "Comprehension" and "Subjective" scores described in section 4. Many researchers, e.g., [2], follow the recommendation of [5] that continuous-value variables be normalized by dividing the individual participant metrics by two times the group standard deviation, to facilitate easier comparison among coefficients of scalar and binary predictors. We have followed this procedure for all of the continuous independent variables in this study.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our dependent variables included the "Comprehension" and "Subjective" scores described in section 4. Many researchers, e.g., [2], follow the recommendation of [5] that continuous-value variables be normalized by dividing the individual participant metrics by two times the group standard deviation, to facilitate easier comparison among coefficients of scalar and binary predictors. We have followed this procedure for all of the continuous independent variables in this study.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We focus on studies that have been conducted with deaf participants in the context of evaluating sign language animations (section 2.1) or to determine general acceptance of such technology (section 2.2). While some researchers have conducted studies of how various demographic or health factors affect technology use and acceptance, e.g., [1, 2,25], this section focuses on studies with deaf participants evaluating sign language animations.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, search difficulties experienced by older people were often explained by age-related declines in cognitive abilities, such as working memory, vocabulary, reasoning, and flexibility (Dommes, Chevalier, & Lia, 2011;Pak & Price, 2008;Queen, Hess, Ennis, Dowd, & Grühn, 2012;Sharit et al, 2008) and/or difficulties in learning new tools (e.g., Stronge et al, 2006). For instance, recent studies have shown that older adults feel more disoriented when browsing websites compared to younger adults because of age-related declines in spatial ability and mental model accuracy (Wagner, Hassanein, & Head, 2014) along with declines in short term memory and problem-solving abilities (Crabb & Hanson, 2014). Dommes et al (2011) particularly showed that lower performance of older people resulted from age-related declines in cognitive flexibility, which is defined as the ability to switch cognitive processing strategies to adapt to unexpected conditions in the environment (Chevalier & Chevalier, 2009;Eslinger & Grattan, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…So, when individual studies took place, particularly those reliant on specific information (such as the results taken from cognitive measures), the participant information was updated. In such cases, where appropriate, the user was retested to discover his or her current score because the researcher was likely to be looking for participants with different levels of fluid intelligence (for example) in order to test whether this impacts on study results [Trewin et al 2012;Crabb and Hanson 2014].…”
Section: Side User Pool Data and Characteristicsmentioning
confidence: 99%